2014
DOI: 10.5005/jp-journals-10024-1561
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Different Angles and Reciprocation on the Shaping Ability of Two Nickel-Titanium Rotary Root Canal Instruments

Abstract: Purpose: The purpose of the present study was to investigate and compare the effect of different reciprocating movements and angles on the shaping ability of the WaveOne and the single-file ProTaper F2 using cone beam computed tomography (CBCT). Materials and methods:The mesiobuccal canals of 40 extracted maxillary molars, with curvatures of 20 to 45° were coded and randomly divided into 4 equal experimental groups according to the instrument used (ProTaper F2 file and WaveOne) and the reciprocation range, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…All of the evaluated combined motions significantly increased the fatigue resistance compared with the CR motion, but they were also significantly different from each other. Accordingly, previous studies have shown that changing the kinematics of the reciprocating motion can significantly affect the fracture resistance of NiTi instruments . The results of our study can be further explained by understanding the effect of each motion on NiTi instruments.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…All of the evaluated combined motions significantly increased the fatigue resistance compared with the CR motion, but they were also significantly different from each other. Accordingly, previous studies have shown that changing the kinematics of the reciprocating motion can significantly affect the fracture resistance of NiTi instruments . The results of our study can be further explained by understanding the effect of each motion on NiTi instruments.…”
Section: Discussionsupporting
confidence: 63%
“…The NCF is useful for comparing different rotary instruments; however, it is not suitable for comparing the performance of different motions (11). Accordingly, previous studies have shown that changing the kinematics of the reciprocating motion can significantly affect the fracture resistance of NiTi instruments (7,(24)(25)(26)(27)(28)(29)(30). Thus, in the present study, the results were expressed as the time to fracture.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations